2013
DOI: 10.1002/adfm.201302158
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Vertically Aligned Tunable Polyaniline on Graphene/ZrO2 Nanocomposites for Supercapacitor Energy‐Storage Application

Abstract: 1312www.MaterialsViews.com wileyonlinelibrary.com . IntroductionWith the rising progress of global economy and industry, the impending energy crisis has stimulated intense research on the low cost, environmentally friendly, and renewable energy resources. [ 1 ] Therefore, great efforts have been devoted to develop low cost electrode materials with high energy density, high power density, and excellent cycling stability. Supercapacitors, can be considered as the supreme candidate of the nextgeneration energy st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(119 citation statements)
references
References 43 publications
(45 reference statements)
2
117
0
Order By: Relevance
“…The Cyclic Voltammetry measurements were done in 1 (M) KCl aqueous electrolyte solution at a potential window from À0.4 to +0.8 V and at different scan rates from 10 mV/s to 100 mV/s. The specific capacitances (C sp ) of PZG composite at different scan rates were calculated on the basis of the following equation [27,29]:…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cyclic Voltammetry measurements were done in 1 (M) KCl aqueous electrolyte solution at a potential window from À0.4 to +0.8 V and at different scan rates from 10 mV/s to 100 mV/s. The specific capacitances (C sp ) of PZG composite at different scan rates were calculated on the basis of the following equation [27,29]:…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…They have observed that specific capacitance value of the composite decreased from %242 F/g to %193 F/g for modification of graphene. Giri et al [29] have developed an electrically conducting (70.8 S cm À1 ) PANI/ graphene/zirconium oxide (ZrO) nanocomposite with high specific capacitance value of %1360 F/g at 1 mV/s.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limitation to use of pure graphene as electrodes for SCs, because graphene sheets can readily aggregation or restacking, leading to a greatly reduced surface area and diffusion rate [16]. Recently, one effective strategy to overcome the drawback is incorporate nanocrystals of transition metal oxides/ hydroxides in form of nanocomposites [17,18]. To date, reduced graphene oxide (rGO) nanosheets have been coupled with various transition metal oxides such as RuO 2 [8], MnO 2 [19], NiO [20], Co 3 O 4 [21], NiCo 2 O 4 [22], etc., to keep the graphene sheets separated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the remaining hole in ZrO 2 takes part in the redox reaction to generate OH, which is further used to remove cadmium ions. Owing to the high specific surface area and superior electron mobility of GO, an appropriate integration of GO and ZrO 2 would give rise to a hybrid nanocomposite to achieve high photodegradation activity [22]. In this case, the recombination of photo-generated electrons and holes is suppressed, and their lifetime is prolonged.…”
Section: Photocatalytic Activity Of Go-zromentioning
confidence: 99%
“…Researchers have also demonstrated that ZrO 2 has a strong affinity to negatively charge moieties [19], which motivated us to use graphene oxide (GO)-ZrO 2 nanocomposite as selective photocatalyst for heavy metals. Moreover, various papers have been published recently on the graphene-ZrO 2 nanocomposites applications, which include the deoxyribonucleic acid sensing detection [20], organophosphorus agents [21], supercapacitor energy-storage application [22], and photocatalytic degradation of antimonite (Sb(III)) and antimonate (Sb(V)) from aqueous solution [23].…”
Section: Introductionmentioning
confidence: 99%